Course Learning Outcomes Evaluation Through Online Assignments (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study explores the potential reasons behind higher scores observed in online quizzes during the COVID-19 pandemic. We hypothesize that factors such as increased test environment comfort, access to resources, technological advantages, adaptation to online learning, motivational changes, and variations in assessment design all contributed to improved student performance in the online format. Our findings support this hypothesis, as online courses exhibited both higher and more consistent Course Learning Outcome (CLO) achievement compared to traditional face-to-face settings. These results suggest that online learning environments may offer certain advantages that can enhance student success.